MENGURAI JERATAN PRAKTIK RENTE KOPERASI ABAL-ABAL Studi Kasus Pada Warung Sembako di Kota Malang - ALERIA IRMA HATNENY; DWI KURNIAWAN EFFENDI; AMELIA SETYAWATI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2023)
The existence of a minimarket network, the proliferation of 24-hour shop chains and the Covid 19 pandemic cannot be denied, that it has increasingly the complicated problems of micro business capital, especially grocery store in urban areas. Will grocery store exist when their business capital relies on fake cooperatives that are increasingly taking advantage of these conditions? Through a phenomenological qualitative approach, its tries to explore the problems surrounding the decision to borrow capital from fake cooperatives by urban grocery store entrepreneurs in Malang City. The results of the study found that the capital problem for grocery store is very complex. Many factors underlie the act of borrowing from fake cooperatives. The bondage of fake cooperative loans creates a capital burden and a wide-reaching impact not only on the urban grocery store business operators, most of whom are women, but also on their families.